A meta analysis on the effectiveness of computer-assisted instruction: Turkey sample - (:unkn) unknown (My University, 2008)
Studies focusing on the effectiveness of computer-assisted instruction have been growing recently in Turkey. In this research, quantitative studies comparing the effectiveness of computer- assisted instruction to traditional teaching method and conducted between 1998 and 2007 are studied by meta analysis. Seventy eight studies that have eligible data were combined with meta analytical methods by coding protocol from the 422 master's and doctoral degree and 124 articles. As a result for the study, the effect size of computer-assisted instruction method for academic achievement calculated 1.048. This is large scale according to Thalheimer and Cook, large and Cohen, Welkowitz and Ewen (2000). Recommendations were made based on the results of the study. © 2008 Eǧitim Danişmanliǧi ve Araştirmalari İletişim Hizmetleri Tic. Ltd. Şti.
Keywords: Computer- Assisted instruction; Computer- Based education; Effect size; Effectiveness; Meta-analysis